Iterative multiuser detection for convolutional coded DS-CDMA communication systems - Pan, Ju Yan (2008)
This thesis deals with the iterative decoding algorithm of the channel coded Direct-Sequence Code Division Multiple Access (DS-CDMA) system with interleaving, or also known as iterative multiuser detection.